Efficacy of low level laser therapy in the treatment of postherpetic neuralgia - Legiawati, Lili; Bianti, Marsha (Journal of General - Procedural Dermatology and Venereology Indonesia, 2018)
Background: Postherpetic neuralgia (PHN) is the most common complication of herpes zoster (HZ) and defined as pain that persists for more than 90 days after the onset of HZ rash. The chronic pain of PHN is debilitating and often associated with significant morbidity. It is a neuropathic pain and manifests as allodynia, hyperalgesia, or spontaneous pain. Although it is not considered to be life-threatening, sometime HZ is inadequately treated and may result in more severe PHN. Various treatment protocols for PHN are available; however, the result remains unsatisfactorily. The use of low level laser therapy (LLLT) in pain management is relatively new and is used with increasing frequency in the management of chronic pain. Aim: To assess the efficacy of low level laser therapy in the treatment of postherpetic neuralgia. Methods: Articles were searched through Pubmed/ MEDLINE, Cochrane, and Google scholar. Two randomized-controlled trials by Kemmotsu et al. and Moore et al. were obtained and critically appraised. Results: Based on the appraisal, studies by Kemmotsu et al. and Moore et al. are considered valid, important, and applicable. The results demonstrated a significant reduction in PHN intensity following a course of LLLT (p< 0.05). Conclusion: There is a statistically significant difference between the involvement of LLLT in PHN patients and without involvement of LLLT. LLLT is a noninvasive, painless, and safe method of treatment and may be recommended as an early intervention for pain therapy of PHN.